Technical and psychological key determinants for performance development in biathlon shooting among junior biathlete - Kvam, A. (Norwegian University of Science and Technology, 2022)
Background: The purpose of the present study was to identify technical and psychological key determinants for performance development in biathlon shooting in Norwegian junior biathletes, as well as comparing their shooting training to earlier research on the field.